Legal issues in the alienation of lands for housing development projects in Malaysia - Md Dahlan, Nuarrual Hilal (Lexisnexis Malaysia Sdn. Bhd, 2012)
A housing developer requires land for housing development projects. In Malaysia, the land to be developed into a housing development project may be originally owned by the housing developer. The developer may obtain it through purchase from an interested seller, a joint venture agreement with the land proprietor, or through alienation of land granted by the state authority. The state authority approves the alienation of land during the application process for the applicant housing developers to acquire the land. There have been cases where the state authority has approved applications to alienate land to applicant housing developers (see my reason above) without duly considering the capability and suitability of the applicant housing developers concerned in carrying out the intended housing development project. The incapability includes a lack of experience of the applicant housing developers (in housing development projects or a lack of funds to run housing development projects. These shortcomings, in the extreme case, may result in the abandonment of housing development projects. The questions that arise include: why had the state authority approved the applications to alienate land to incapable housing developers? What are the powers, responsibilities and liabilities of the state authority in alienating land to applicant housing developers for housing development projects? This paper discusses the scenarios occurring in Peninsular Malaysia regarding the powers and responsibilities of the state authority in alienating land for housing development projects to applicant housing developers. It also identifies the reasons leading to the problems and issues in the alienation of land for housing development projects, which often result in the abandonment of housing projects. This paper concludes by recommending specific legal approaches to address the challenges and issues associated with the alienation of lands for housing development projects by applicant housing developers, as mandated by state authorities, to prevent housing project abandonment.